Hematological parameters of health status in the common toad Bufo arenarum in agroecosystems of Santa Fe Province, Argentina - Cabagna, Mariana C. (2005)
We compared some hematological parameters and values of plasma cholinesterase activity in adult Bufo arenarum from a control site and agricultural sites. The mean values of the plasma cholinesterase activity did not vary among toads collected in pristine forest and agricultural sites. The blood parameters (hematocrit, hemoglobin concentration, white blood cells, and heterophils) from agricultural sites differed from the control site. The results suggest a high pesticide impact from intensive cropping in mid-eastern Santa Fe Province of Argentina.